The Development of Web Learning Based on Project in The Learning Media Course at IAIN Kendari - Ambar Sri Lestari (Jurnal Pendidikan Islam, 2019)
This study aims to explain the development of multimedia through project-based learning. The method used in this study is development research (R & D) depleted to analyze the learning products results. The object of this research is 30 students of PAI (Pendidikan Agama Islam/Islamic Education) study program in learning media. The data were collected using observation on students' presentation before using multimedia, doing an interview to identify students' argumentation in delivering the material before and after using multimedia presentation and product test through the individual test, small group test and field study test. Multimedia development procedures were using the ADDIE model, namely: Analysis, Design, Development, Implementation and Evaluation. The results showed that the teaching of multimedia based on Project Based Learning could improve the student learning mastery as for the whole process is interactive and interesting, giving the students the opportunity to be creative and innovative in making multimedia teaching materials. Multimedia teaching materials were stored on youtube and can be viewed on web e-learning http: //www.elearning-ambarsrilestari.web. id. In addition, paper materials were uploaded on blogs, while module teaching materials were uploaded on Slideshare stored on e-portfolio on www.ambarsrilestari.web.id.